Best Practice: Profil Pelajar Pancasila in English Teaching of SMAN 2 Pare - Indriana, Sisilia Candra Hadi (ELLITE, 2023)
The introduction of a new curriculum, known as the Merdeka curriculum, has fundamentally altered various vital aspects, including character education. Merdeka curriculum provides Indonesian character education with a new paradigm, Profil Pelajar Pancasila. However, it can be challenging for English teachers to include activities based on the Pancasila ideals and the foreign culture in their lessons. The study portrays how English teachers of SMAN 2 Pare plan, carry out, and evaluate Profil Pelajar Pancasila in teaching activities. This descriptive qualitative study collected data from three English teachers of SMAN 2 Pare through interviews, classroom cobservations, and document analysis. The findings showed that the teachers conducted the application of Profil Pelajar Pancasila in teaching in three steps: planning, classroom practice, and assessment. Various learning activities and forms of tasks were synced with the profile elements in targeted materials. For the assessment, the teachers used self-designed rubric to regularly observe the students’ engagement in Profil Pelajar Pancasila before releasing the numerical and descriptive report. Although facing difficulties to implement values of morals to nation and global diversity, the teachers could familiarize the pupils with the foreign culture while ensuring they maintained their identity as Pancasila students. Furthermore, the result helps English teachers acquire practical advice regarding using Profil Pelajar Pancasila in foreign language teaching.